PENGARUH PERTUMBUHAN ASET LABA BERSIH DAN ARUS KAS OPERASI TERHADAP KEBIJAKAN DIVIDEN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERBANKAN DI BURSA EFEK INDONESIA TAHUN 2018-2022) - Yuliyana, Sinta; Muanifah, Suciati (Jurnal Nusa Akuntansi, 2024)
This study aims to test and obtain empirical evidence regarding the Effect of Asset Growth, Net Profit, and Operating Cash Flow on Dividend Policy. The population in this study are banking sector companies listed on the Indonesia Stock Exchange in 2018-2022. The data used is secondary data using Purposive Sampling sampling techniques. The population used in this study were 45 companies with 13 selected companies with a total sample of 65 data. The analysis technique used in this study is panel data regression. The results of the study show that simultaneously Asset Growth, Net Profit and Operating Cash Flow together affect Dividend Policy. while partially Asset Growth does not affect Dividend Policy where the rise and fall of assets will not affect Dividend Policy, Net Profit has a significant effect on Dividend Policy meaning that net profit can be used as absolute information in predicting dividends that will be received by investors in the current period. While Operating Cash Flow does not have a significant effect on Dividend Policy, this shows that operating cash flow is not the main determining factor in dividend distribution policy.